2001
DOI: 10.1046/j.1365-2109.2001.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating effects of pond water on digestive enzyme activity in the Pacific white shrimp,Litopenaeus vannamei(Boone)

Abstract: Crude enzyme extracts were obtained from the digestive glands of Paci®c white shrimp, Litopenaeus vannamei (Boone), reared in oligotrophic well water and eutrophic shrimp pond water to compare digestive enzyme activity between the two groups. Speci®c activities of serine protease, collagenase, amylase, cellulase, lipase and acid phosphatase were signi®cantly higher (P < 0.01) in pond water-reared shrimp (PW shrimp) than in well water rearedshrimp (WW shrimp). For most enzymes assayed, speci®c activity was more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 43 publications
2
82
1
2
Order By: Relevance
“…It is possible that biofloc plays a role in stimulating the activities of digestive enzymes (Moss et al, 2001;Xu et al, 2012a;Xu et al, 2012b). In addition, Xu and Pan (2012) found that biofloc displayed relatively high amylase activities, which may account for the increased intestinal amylase activity of fish growing in the BFT treatment in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…It is possible that biofloc plays a role in stimulating the activities of digestive enzymes (Moss et al, 2001;Xu et al, 2012a;Xu et al, 2012b). In addition, Xu and Pan (2012) found that biofloc displayed relatively high amylase activities, which may account for the increased intestinal amylase activity of fish growing in the BFT treatment in this study.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…Shrimps grown in biofloc are speculated to change digestive enzyme activities in response to the changes in the diet conditions (Le Moullac et al, 1996;. The biofloc is presumed to enhance the production or activity of the digestive enzymes which in turn contributed to the better growth and feed utilization (Moss et al, 2001;Xu et al, , 2013.…”
Section: Digestive Enzyme Activitymentioning
confidence: 99%
“…Consequently, from the digestive enzyme profile it is possible to predict the ability of the species to use different nutrients. Since the digestive enzyme activity is high for those substrates that are more common in the diet (Moss et al, 2001) there is a common belief that the activity of digestive enzymes can be boosted by providing certain nutrients into the diet for an adequate amount of time.…”
Section: Binder Effect On Digestive Enzymesmentioning
confidence: 99%